Measurement Issues: Neuropsychological assessment with children and adolescents; unlocking the mysticism, methods and measures with the help of Tom Swift. Issue 2 (6th November 2013) - Tonks, James; Yates, Phil J.; Williams, Huw W.; Frampton, Ian; Slater, Alan
<x xml:space="preserve">Abstract</x> Background and Scope In this article, we provide a brief overview of the principles that guide paediatric neuropsychological assessment, the methods used and some examples of the measures available. Findings We explore intellectual, adaptive and social functioning from a neuropsychological perspective and describe suitable measures for use in paediatric neuropsychological assessment in each domain. Conclusions We provide an example of assessment and interpretation using a fictional character (Tom Swift) to demonstrate that neuropsychological assessment is important in understanding the everyday questions that arise in children's services around risk, needs, level of understanding and capacity to engage with services.